Specification of multi-resolution modeling space for multi-resolution system simulation. (January 2013) - Hong, Su-Youn; Kim, Tag Gon
Multi-resolution modeling (MRM) represents a real system as a set of models of different resolutions, at different abstraction levels, from the viewpoint of simulation objectives. MRM is a significant technology for complex and large-scale simulation. However, previous research is almost application specific and dependent on a specific simulation algorithm. The concepts separate multi-resolution models from the simulation models, thereby making them adaptable to any existing simulation methodology. This paper proposes a specification of multi-resolution modeling space (MRMS) for multi-resolution system simulation. The proposed specification is based on concepts of decoupling MRM and multi-resolution simulation. This MRMS specification supports MRM in two parts: resolution conversion for dynamically changing simulation model structures and resolution matching interfaces between events in different resolutions. A simple example demonstrates advantages of the proposed specification.